Rapid and fatal meningococcal disease due to a strain of Neisseria meningitidis containing the capsule null locus. - Hoang, L; Thomas, E; Tyler, S; Pollard, A; Stephens, G; Gustafson, L; McNabb, A; Pocock, I; Tsang, R; Tan, R (Oxford University Press, 2005)
Background. Neisseria meningitidis continues to be an important cause of invasive bacterial disease among children and young adults worldwide. In Canada, N. meningitidis strains that bear serogroups B and C polysaccharide capsules predominate. We report the first documented case of invasive meningococcal disease in an immunocompetent host caused by an acapsular strain of N. meningitidis containing the capsule null locus (cnl). Methods. Analysis of the isolate was performed with use of serological and molecular methods, including multilocus sequence typing and cnl gene identification. Analysis of 16S ribosomal RNA (rRNA) and porA genes was also performed to confirm the identity of the bacterium. Results. The patient was a healthy, immunocompetent 13-year-old child, and N. meningitidis was recovered from a sample of her cerebrospinal fluid before death. The isolate was nontypeable by both conventional antisera and indirect whole-cell enzyme-linked immuosorbent assay methods using antibodies to serogroups B, C, Y, and W135. The isolate was further identified as a cnl strain, serotype 15 (ST-198). N. meningitidis–specific DNA was identified in the isolate and in the pre- and postmortem specimens by 16S rRNA and porA gene analysis. Conclusions. This is the first reported case of fatal meningococcal disease caused by an acapsular cnl strain of N. meningitidis that was isolated from an immunocompetent host. Routine molecular diagnostic methods targeted at the cnl locus failed to detect this organism, indicating a need to determine the incidence of infection with cnl strains among patients with culture-negative invasive disease.